Penemuan hukum Islam di Indonesia dengan sinergi Pancasila dan dalil muttafaq - gustian, aisyah (Maliki Interdisciplinary Journal, 2026)
Judges carry out a commitment to justice, this is the vision of the judiciary. The object of this research is related to the discovery of law in synergy with Pancasila and the muttafaq argument, realizing justice based on Pancasila, especially the first principle. Then, the author implements a qualitative normative juridical research approach with the synergy of the muttafaq argument. Indonesia is a state of law, all laws in Indonesia are sourced from Pancasila, if there is a void, ambiguity, or no legal regulations, then the judge makes a legal discovery that is obliged to be oriented towards Pancasila and the Constitution to synergize legal discovery, without reducing the obligation to conduct ijtihad, istinbath and study Islamic law from the muttafaq argument. There is also Article 2 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power, so this becomes a guideline for judges in carrying out their duties that they are not only mouthpieces of the law.